Left $φ$-biflatness and $φ$-biprojectivity of certain Banach algebras with applications - Solaleh Salimi; Amin Mahmoodi; Mehdi Rostami; Amir Sahami (AUT Journal of Mathematics and Computing)
This paper continues the investigation initially begun in \cite{srp1}. We show that left $φ$-biflatness and left $φ$-biprojectivity are closely related to the notions of left $φ$-amenability and $φ$-inner amenability. We characterize left $φ$-biprojectivity and left $φ$-biflatness of certain semigroup algebras and some algebras related to a locally compact group. We discuss non left $φ$-biflatness of some specified triangular Banach algebras.